Pretreatment immune-inflammatory prognostic score in predicting clinical outcomes in esophageal squamous cell carcinoma receiving neoadjuvant immunochemotherapy - Zhao, Qiang; Wang, Liang; Yang, Xun; Feng, Jifeng; Chen, Qixun (Frontiers in Immunology, 2025)
PurposeIn this research, we established, for the first time, an immune-inflammatory prognostic score (IIPS) reflecting the balance of immune and inflammatory status to explore its prognostic value in patients with esophageal squamous cell carcinoma (ESCC) receiving neoadjuvant immunochemotherapy (NICT).MethodsIn this retrospective study, two hundred and five ESCC patients who received NICT were included. To ascertain whether IIPS was superior to other traditional immune-inflammatory indices (IIIs), we compared their predictive values. The association between IIPS and overall survival (OS)/disease-free survival (DFS) was also investigated. For survival analyses, the Kaplan-Meier method and Cox proportional hazard regression analyses were employed.ResultsWith a mean age of 64 years (range: 45–75 years), there were 181 (88.3%) males and 24 (11.7%) females. Sixty-four (31.2%) patients achieved pCR after NICT. A total of 79 (38.5%) patients relapsed, and 55 (26.8%) cases died. The connection between DFS/OS and IIPS suggested that their interaction was non-linear. The restricted cubic spline (RCS) model identified 200 as the ideal cutoff point for IIPS. Patients exhibiting high IIPS demonstrated significantly worse 3-year OS (63.7% vs. 82.5%, P =0.002) and DFS (47.1% vs. 75.7%, P <0.001) compared to those with low IIPS. Based on the results of the Cox regression analyses, IIPS was a predictor of OS (hazard ratio [HR] =1.864, 95% CI =1.053-3.301, P =0.033) and DFS (HR =2.225, 95% CI =1.376-3.597, P =0.001).ConclusionThe treatment efficacy of NICT for ESCC can be predicted by pretreatment IIPS. IIPS is an innovative, sensitive, and useful index that helps clinicians giving individualized treatments because of improved prognostic stratification.